The Effect of Memorizing the Qur'an on Students' Learning Outcomes and Mathematics Learning Discipline in Grade Xi of Madrasah Tarbiyah Islamiyah (MTI) Canduang - Nisa Oktavia; Vivi Ramdhani; M. Imamuddin; Tasnim Rahmat (Darul Yasin Al Sys, 2026)
This study is driven by the low mathematics achievement of Grade XI students at Madrasah Tarbiyah Islamiyah (MTI) Canduang in the midterm examination. Preliminary observations indicated that students showed greater engagement with religious subjects than with general subjects, which may influence their mathematics learning outcomes. Differences in mathematics achievement were also observed between students with strong and weak Qur’an memorization abilities, while some students demonstrated relatively low learning discipline. This study aims to examine the effect of Qur’an memorization on mathematics learning outcomes and mathematics learning discipline among Grade XI students at MTI Canduang. A quantitative approach with a correlational research design was employed. The population consisted of all Grade XI students at MTI Canduang, comprising six classes with a total of 168 students. A sample of 34 students was selected through random sampling after normality and homogeneity of variance tests were conducted on the population. Data were collected through documentation of Qur’an memorization scores, mathematics achievement tests, and questionnaires measuring students’ mathematics learning discipline. The data were analyzed using simple linear regression. The findings show that Qur’an memorization had a positive effect on students’ mathematics learning outcomes, as indicated by the regression equation Y₁ = 7.765 + 0.900X, a correlation coefficient of 0.646, which reflects a strong positive relationship, and a coefficient of determination of 41.70%. The significance test showed that tcount > ttable, namely 4.784 > 2.037. Furthermore, Qur’an memorization had a significant effect on students’ mathematics learning discipline, as indicated by the regression equation Y₂ = -49.184 + 2.305X, a correlation coefficient of 0.826, which reflects a very strong positive relationship, and a coefficient of determination of 68.2%. The significance test also showed that tcount > ttable, namely 8.278 > 2.037. This study concludes that Qur’an memorization significantly contributes to improving mathematics learning outcomes and mathematics learning discipline among Grade XI students at MTI Canduang. These findings provide theoretical implications for understanding the relationship between religious learning practices and academic behavior, as well as practical implications for integrating discipline-building strategies in mathematics learning within Islamic educational contexts.